Pressure Pain Threshold in Patients With Chronic Pain: A Systematic Review and Meta-Analysis. (July 2021) - Amiri, Mohammadreza; Alavinia, Mohammad; Singh, Manveer; Kumbhare, Dinesh
Abstract : Introduction: In chronic pain conditions, the pressure pain threshold has been used to investigate the presence of central sensitization. Methods: A systematic review and meta-analysis were conducted to compare the threshold in chronic pain patients and healthy individuals. Ovid MEDLINE and Embase up to July 2019 were used to conduct the search. Search strategy included terms and sets of terms that describe the concepts "sensory testing" and "pain measurement." Results: The included studies consisted of 24 were case-control studies and 12 cross-sectional studies. The pooled total sample size was 1280 cases of patients with different diagnoses of chronic pain and 1463 healthy controls. Among the included studies, 32 reported a significant decrease of the pressure pain threshold among patients compared with the controls and four reported no statistically significant difference. The pooled pressure pain threshold mean difference was −1.17 (95% confidence interval = −1.45 to −0.90). There was, however, evidence of significant heterogeneity across the studies ( I 2 = 87.42%, P < 0.001). Conclusions: Patients who experience chronic pain have a significantly lower pressure pain threshold compared with healthy controls. Future research is needed to elucidate factors attributed to the change in pressure pain threshold among patients with chronic pain, as well as the time that the central sensitization occurs. Abstract : Supplemental digital content is available in the text.